Loss of expression of N-acetylglucosaminyltransferase Va results in altered gene expression of glycosyltransferases and galectins - Guo, Hua-Bei (2008)
We isolated mouse embryo fibroblasts (MEFs) from N-acetylglucosaminyltransferase Va (GnT-Va) knockout mice and studied the effects of loss of expression of GnT-Va on asparagine- linked glycans (N-glycan) synthesis and the gene expression of groups of glycosyltransferases and galectins. Loss of GnT-Va expression caused aberrant expression of several N-glycan structures, including N-linked β(1,6) branching, poly-N-lactosamine, bisecting N-acetylglucosamine (GlcNAc) and sialic acid. Using quantitative reverse transcriptase-PCR (qRT-PCR), altered gene expression of several groups of glycosyltransferases and galectins was observed in GnT-Va null MEFs, supporting the observed changes in N-glycan structures. These results suggest that genetic disruption of GnT-Va ultimately resulted in altered MEFs gene expression and decreased tumor progression associated with loss of GnT-Va observed may result in part from a combination of effects from these altered gene expressions.